Kidzone - McManus, Alexandra; White, James; Newton, Wendy; Howieson, J; Storey, Jessica; McManus, Jennifer (Centre of Excellence Science Seafood & Health (CESSH), 2010)
The Centre of Excellence for Science, Seafood and Health has developed a suite of educational resources aimed at increasing awareness of the health benefits of seafood within a healthy diet. All the information presented is evidence based and has been thoroughly researched by the scientific staff of CESSH. Dissemination of resources is one part of a multifaceted approach aimed at increasing awareness of the importance of seafood within a health diet. These resources have been developed by education specialists with extensive experience both with Australia and internationally from kindergarten through to a tertiary level of education. Resources currently available include:Primary Resources are appropriate for Years 3 and 4 and are easily downloadable from http://cessh.curtin.edu.au/kidzone/. The Amazing Omega 3s is an interactive online game that teaches children the omega 3 content of different seafood and is supported by two worksheets. Seafood the Superfood is an online resource where children can highlight different parts of the body in order to determine which nutrients found in seafood support which bodily functions; this is supported by a crossword. Awesome Aquaculture provides educational support for learning about aquaculture. Available online are a teachers manual and 27 page workbook.Secondary Resources have been developed to fit within the current health curriculum framework for Year 12. The teachers resource package includes a group activity in spatial mapping, a critical media review, student presentations and fact sheet and the development of a health survey for fish and seafood consumption that can be carried out within the school environment.